"Are We There Yet?" Quest for Treatment of Refractory Epilepsy. Issue 1 (January 2019) - Velíšek, Libor
Biochemical Autoregulatory Gene Therapy for Focal Epilepsy Lieb A, Qiu Y, Dixon CL, Heller JP, Walker MC, Schorge S, Kullmann DM. Nat Med . 2018;24:1324-1329. doi:10.1038/s41591-018-0103-x Despite the introduction of more than one dozen new antiepileptic drugs in the past 20 years, approximately one-third of people who develop epilepsy continue to have seizures on mono- or polytherapy. Viral-vector-mediated gene transfer offers the opportunity to design a rational treatment that builds on mechanistic understanding of seizure generation and that can be targeted to specific neuronal populations in epileptogenic foci. Several such strategies have shown encouraging results in different animal models, although clinical translation is limited by possible effects on circuits underlying cognitive, mnemonic, sensory, or motor function. Here, we describe an autoregulatory antiepileptic gene therapy, which relies on neuronal inhibition in response to elevations in extracellular glutamate. It is effective in a rodent model of focal epilepsy and is well tolerated, thus lowering the barrier to clinical translation.